Pengaruh Perencanaan Pajak Terhadap Nilai Perusahaan Dengan Audit Internal Dan Eksternal Sebagai Pemoderasi - Nurifa Laksmitasari Azizah (Fakultas Ekonomika dan Bisnis Universitas Selamat Sri, 2022)
This study aims to examine the effect of tax planning on firm value. In addition, the study also tested the KAP's external audit and internal audit, namely the audit committee in moderating the effect of tax planning on firm value. The research sample is 75 manufacturing companies listed on the IDX in 2018-2020. The test results show that tax planning has a significant effect on firm value. The moderating aspect is obtained from the use of KAP external audit variables but the internal audit audit committee is not able to moderate the relationship between tax planning and firm value.